2010
DOI: 10.3390/ph3040994
|View full text |Cite
|
Sign up to set email alerts
|

Antiproliferative Properties of Type I and Type II Interferon

Abstract: The clinical possibilities of interferon (IFN) became apparent with early studies demonstrating that it was capable of inhibiting tumor cells in culture and in vivo using animal models. IFN gained the distinction of being the first recombinant cytokine to be licensed in the USA for the treatment of a malignancy in 1986, with the approval of IFN-α2a (Hoffman-La Roche) and IFN-α2b (Schering-Plough) for the treatment of Hairy Cell Leukemia. In addition to this application, other approved antitumor applications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
123
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(124 citation statements)
references
References 116 publications
(134 reference statements)
1
123
0
Order By: Relevance
“…IFNs are normally present at low levels in plasma, which presumably plays an antiviral and antitumor surveillance role. 42,43 IFN promotes apoptosis of a variety of tumor cell types 44,45 and it has anti-angiogenic properties. 44,46 Hence, this network could be deregulated since several genes related to IFN are hypermethylated like IL23 28 and IL27, 47 which could contribute to the pathogenesis of transformed MPNs.…”
Section: Discussionmentioning
confidence: 99%
“…IFNs are normally present at low levels in plasma, which presumably plays an antiviral and antitumor surveillance role. 42,43 IFN promotes apoptosis of a variety of tumor cell types 44,45 and it has anti-angiogenic properties. 44,46 Hence, this network could be deregulated since several genes related to IFN are hypermethylated like IL23 28 and IL27, 47 which could contribute to the pathogenesis of transformed MPNs.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of these different functions, it was revealed that the coordination and cooperation of multiple distinct signaling cascades are required for response to interferon. Thereby, these induce transcription of interferon-stimulated genes (ISGs) that are involved in anti-proliferation, anti-invasion and antimetastasis activity (14,15). MMP9 is one of the ISGs and is involved in proteolytic degradation of the extracellular matrix, which is a critical step in tumor invasion.…”
Section: Introductionmentioning
confidence: 99%
“…Type 1 interferons (IFNs), mainly IFN-a and IFN-b, have been shown to have potent in vitro and in vivo antitumor activities in several tumors (Vitale et al 2007, Bekisz et al 2010, Erdmann et al 2011. In most studies, IFN-b is considerably more potent than IFN-a in its antitumor effect.…”
Section: Introductionmentioning
confidence: 99%